Endophilin-A2 dependent VEGFR2 endocytosis promotes sprouting angiogenesis - Genet, Gael; Boyé, Kevin; Mathivet, Thomas; Ola, Roxana; Zhang, Feng; Dubrac, Alexandre; Li, Jinyu; Genet, Nafiisha; Henrique Geraldo, Luiz; Benedetti, Lorena; Künzel, Steffen; Pibouin-Fragner, Laurence; et al. (Nature communications, 2019)
Endothelial cell migration, proliferation and survival are triggered by VEGF-A activation of VEGFR2. However, how these cell behaviors are regulated individually is still unknown. Here we identify Endophilin-A2 (ENDOA2), a BAR-domain protein that orchestrates CLATHRIN-independent internalization, as a critical mediator of endothelial cell migration and sprouting angiogenesis. We show that EndoA2 knockout mice exhibit postnatal angiogenesis defects and impaired front-rear polarization of sprouting tip cells. ENDOA2 deficiency reduces VEGFR2 internalization and inhibits downstream activation of the signaling effector PAK but not ERK, thereby affecting front-rear polarity and migration but not proliferation or survival. Mechanistically, VEGFR2 is directed towards ENDOA2-mediated endocytosis by the SLIT2-ROBO pathway via SLIT-ROBO-GAP1 bridging of ENDOA2 and ROBO1. Blocking ENDOA2-mediated endothelial cell migration attenuates pathological angiogenesis in oxygen-induced retinopathy models. This work identifies a specific endocytic pathway controlling a subset of VEGFR2 mediated responses that could be targeted to prevent excessive sprouting angiogenesis in pathological conditions. VEGF-A/VEGFR2 signaling is a key driver of endothelial cell migration during sprouting angiogenesis. Here Genet et al. show that endophilin A2 regulates these processes by mediating clathrin-independent VEGFR2 internalization.